2018
DOI: 10.1371/journal.pone.0205276
|View full text |Cite
|
Sign up to set email alerts
|

A control mechanism for intra-mural peri-arterial drainage via astrocytes: How neuronal activity could improve waste clearance from the brain

Abstract: The mechanisms behind the clearance of soluble waste from deep within the parenchyma of the brain remain unclear. Experimental evidence reveals that one pathway for clearance of waste, termed intra-mural peri-arterial drainage (IPAD), is the rapid drainage of interstitial fluid along basement membranes (BM) of the smooth muscle cells of cerebral arteries; failure of IPAD is closely associated with the pathology of Alzheimer’s disease (AD), but its driving mechanism remains unclear. We have previously shown tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The macroscopic changes in CSF flow we identified are expected to alter waste clearance, as pulsatile fluid dynamics can increase mixing and diffusion (20,21,36). Neurovascular coupling has been proposed to contribute to clearance (37), but why it would cause higher clearance rates during sleep was not known. Our study suggests slow neural and hemodynamic oscillations as a new possible contributor to this process, in concert with other physiological factors.…”
Section: One Sentence Summarymentioning
confidence: 98%
“…The macroscopic changes in CSF flow we identified are expected to alter waste clearance, as pulsatile fluid dynamics can increase mixing and diffusion (20,21,36). Neurovascular coupling has been proposed to contribute to clearance (37), but why it would cause higher clearance rates during sleep was not known. Our study suggests slow neural and hemodynamic oscillations as a new possible contributor to this process, in concert with other physiological factors.…”
Section: One Sentence Summarymentioning
confidence: 98%
“…Overactivation of the classical RAS may also reduce clearance of Aβ. Intra-mural peri-arterial drainage (IPAD) and para-vascular glymphatic channels have been implicated in the removal of Aβ from the brain [183][184][185]. The functioning of these drainage pathways depends on the polarised expression of aquaporin-4 in astrocytic endfeet [186], which is regulated by pericytes [187].…”
Section: Potential Neurological Consequences Of Increased Classical Rmentioning
confidence: 99%
“…In keeping with this hypothesis, it was observed that inhibition of CAs with AAZ reduces CSF secretion by half in rats [85]. However, clearance of brain products is driven by both CSF movements and vascular pulsatility [86,87]. AAZ is clinically used to increase cerebral blood flow and vasoreactivity [88,89].…”
Section: Altered Carbonic Anhydrases Expression and Activity In Nementioning
confidence: 99%